ITGA4 genetic variants as a predictor of therapeutic responsivity to autoimmune diseases - De Matos, Matheus D.; Guimenes, Bárbara D.; Pavani, Giovanni K.; Fernandes, Gabriel Gripp; Montes, Guilherme C.; Fontes-Dantas, Fabrícia L. (Frontiers in Pharmacology, 2026)
Integrins are pivotal adhesion receptors that mediate dynamic communication between cells and their surrounding environment. Through bidirectional signaling, they regulate key physiological processes such as cell migration, inflammation, and tissue organization. Among them, the α4 integrin subunit, encoded by the ITGA4 gene, forms α4β1 (VLA-4) and α4β7 heterodimers, both essential for leukocyte adhesion and migration across inflamed tissues and blood–brain barrier. Variability in therapeutic response to α4 integrin inhibitors, such natalizumab, highlights the need to clarify the genetic and molecular determinants that regulate ITGA4 function. This mini review provides an updated overview of ITGA4 from historical, biological, and pharmacogenetic perspectives. We summarize current evidence linking ITGA4 genetic variants with disease susceptibility, progression, and therapeutic outcomes in autoimmune and neuroinflammatory disorders. Finally, we discuss existing limitations, population inconsistencies, and emerging strategies integrating multi-omic and in silico analyses to translate ITGA4 variants into predictive biomarkers for personalized immunotherapy.